Social Media as Supporting Media in Online Tutorial: The case of Communication Science Students Program of Universitas Terbuka (Universitas Terbuka, 2023)
The Covid-19 pandemic has significantly impacted to various sectors, especially distance higher education. During the pandemic, almost everyone accessed the internet, which reduced performance when accessing online tutorials. In terms of the quantity of students participating in online tutorials tends to increase but in terms of the quality of students' activeness in accessing tutorials is not optimally. This study identifies a number of elements that contribute to the poor quality of online tutorial access. This study uses mix method which starting with online survey and continuing with interviews in focus group discussion in three Regional Offices. The respondents are enrolled in semesters 3, 5, and 7. The results show that over three quarters of respondents use Android smartphones, and they range in age from 18 to 21. The top three social media respondents using are Line, Instagram, and Telegram. The ability to manage learning is quite strong, and access to social media is very high. This condition can help them in improving interaction between students and tutors. In the future it need to develop an tutorial application that is handy and comprehensive one.